Application of Non-Model Dependent Hybrid Higher-Order Differential Feedback Controller on Crane System - Tahir, Nura Musa; Liman, Haliru; Godwin, Sani; Anene, Ejike C.; Shehu, Yakubu; Alhassan, Ahmad Bala (International Journal of Integrated Engineering, 2020)
Gantry Crane is a machine used for shipping of goods from one point to another. Speed, accuracy and safety are of paramount importance in gantry crane (GC) operation, but operating GC results in unwanted sway which degrades the accuracy and safety. In this paper, hybrid control schemes are proposed for precise trolley position control and sway suppression in GC systems. Output Based input shaping (OBIS) filter was designed using the output of the system for sway suppression and proportional integral derivative (PID), linear quadratic regulator (LQR), higher order differential feedback (HODF) controllers were incorporated separately for precise trolley position control. Based on Simulation studies and analysis, it was observed that LQR-OBIS controller shown more precise tracking and higher sway reduction control. But HODFC-OBIS is a model-free control schemes hence more robust.